The intellectual world of C.S. Lewis - McGrath, Alister E., 1953- (Chichester, West Sussex, UK : Wiley-Blackwell, a John Wiley & Sons, Ltd., Publication, 2014)
"Marking the 50th anniversary of Lewis' death, The Intellectual World of C. S. Lewis sees leading Christian thinker Alister McGrath offering a fresh approach to understanding the key themes at the centre of Lewis' theological work and intellectual development. This book: Brings together a collection of original essays exploring important themes within Lewis' work, offering new connections and insights into his theology ; Throws new light on subjects including Lewis' intellectual development, the uses of images in literature and theology, the place of myth in modern thought, the role of the imagination in making sense of the world, the celebrated 'argument from desire', and Lewis' place as an Anglican thinker and a Christian theologian ; Written by Alister McGrath, one of the world's leading Christian thinkers and authors; this exceptional pairing of McGrath and Lewis brings together the work of two outstanding theologians in one volume."--Publisher's website.
A brief biography of C.S. Lewis -- The enigma of autobiography : critical reflections on Surprised by joy -- The "new look" : Lewis's philosophical context at Oxford in the 1920s -- A gleam of divine truth : the concept of myth in Lewis's thought -- The privileging of vision : Lewis's metaphors of light, sun, and sight -- Arrows of joy : Lewis's argument from desire -- Reason, experience, and imagination : Lewis's apologetic method -- A "mere Christian" : Anglicanism and Lewis's religious identity -- Outside the "inner ring" : Lewis as a theologian.
Includes bibliographical references and index.
"Works by Lewis cited": page [185].
Keywords: Lewis, C. S. -- 1898-1963 -- Philosophy; Lewis, C. S. -- 1898-1963 -- Criticism and interpretation; Christian literature, English -- History and criticism